Pengaruh Profitabilitas, Sturktur Modal dan Ukuran Perusahaan terhadap Kualitas Laba dengan Kepemilikan Manajerial sebagai Variabel Moderating - Siti Lusiani; Muhammad Khafid (Politeknik Ganesha Medan, 2022)
The purpose of this study is to find empirical evidence regarding the effect of profitability, capital structure, and firm size on earnings quality with managerial ownership as a moderating variable. The sampling technique was determined by purposive sampling method which was based on the criteria set by the researcher and resulted into 79 units of analysis as observation object. The population in this study are manufacturing companies listed in the Indonesia Stock Exchange during 2016 to 2019 period. The data was collected using documentation method. The data was analysis used descriptive statistical analysis and moderate regression analysis with the tools IBM SPSS Statistic 21. The result of this study proves empirically that profitability and capital structure have an effect to earnings quality. Meanwhile firm size does not affect earnings quality. Furthermore, managerial ownership is able to moderate the effect of profitability and capital structure on earning quality. However, managerial ownership can not moderate the effect of firm size on earning quality. Future research are suggeste to expand the sample of companies from various sectors and increase the research period. Furthermore, it is recommended to add other variabels which might effect earnings quality. Regarding variable measurement it is also suggested to use another method measure each variable.